Relasi Agama dan Kearifan Lokal dalam Tradisi Ter-Ater di Pamekasan, Indonesia - Holis, Khoirul; Silvia, Atik (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
This study aims to reveal Islamic values contained in the Ter-ater tradition in Pamaroh Village, Kadur District, Pamekasan Regency, Indonesia. Ter-ater tradition is a cultural heritage in the Madura island carried out at certain moments, when people deliver food to neighbors and relatives. This tradition also involves activities such as tahlil and prayer together before food is distributed. While using qualitative research method with a semiotic approach, data were collected through interviews, field observations, and related literature studies. After analysing the data, we found the existence of Islamic values in the Ter-ater tradition. These values include fostering mutual care through silaturahmi, strengthening solidarity in the form of ukhuwah Islamiyyah, and maintaining good habits through acts of almsgiving. The results of the research can be a valuable source of information in preserving and strengthening this tradition, as well as increasing religious understanding and awareness of the people of Pamaroh Village.